Dynamic Brillouin cooling for continuous optomechanical systems - Zhu, Changlong; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Cooling a mechanical oscillator to its quantum ground state by overcoming the effects of thermal environment has always attracted great interests [1-3]. Preparing a single mode mechanical oscillator to its ground state has been realized in cavity optomechanics by using sideband cooling. Beyond the cooling of single mode mechanical mode, lots of novel phonon cooling methods for multimode have been proposed recently for extended optomechanical platforms with many degrees of freedom. The intriguing limit of these cases is quantum ground state cooling in continuous optomechanical systems. Brillouin-based technologies provide cooling for groups of phonons in continuous optomechanical systems [4,5]. However, the large mechanical loss, which exceeds optical loss, limits the optomechanical continuum cooling. For general backward Brillouin scattering with higher frequency and thus lower Q-factor, it was thought that it is impractical for ground-state cooling in continuous optomechanical systems.
CRIS-Team Scopus Importer:2024-12-16